An In-Depth Review on Direct Additive Manufacturing of Metals - Azam, F.I. (Institute of Physics Publishing, 2018)
Additive manufacturing (AM), also known as 3D Printing, is a revolutionary manufacturing technique which has been developing rapidly in the last 30 years. The evolution of this precision manufacturing process from rapid prototyping to ready-to-use parts has significantly alleviated manufacturing constraints and design freedom has been outstandingly widened. AM is a non-conventional manufacturing technique which utilizes a 3D CAD model data to build parts by adding one material layer at a time, rather than removing it and fulfills the demand for manufacturing parts with complex geometric shapes, great dimensional accuracy, and easy to assemble parts. Additive manufacturing of metals has become the area of extensive research, progressing towards the production of final products and replacing conventional manufacturing methods. This paper provides an insight to the available metal additive manufacturing technologies that can be used to produce end user products without using conventional manufacturing methods. The paper also includes the comparison of mechanical and physical properties of parts produced by AM with the parts manufactured using conventional processes. Â© Published under licence by IOP Publishing Ltd.